The use of digital image analysis in the discipline of unit operations for the characterization of sand particles (REMUNOM, 2025)
Morphological and geometrical parameters can lead to the understanding of important characteristics concerning the particles under analysis, as to their shape and geometry. This characterization becomes important to the study, as it provides precise details of the particle that can help in the analysis. This study used sand grains in order to determine their morphometric parameters, so a public domain digital imaging software, ImageJ, was used. The software showed great efficiency in image processing and analysis, delivering results of parameters of great importance in the process as particle area, perimeter, major axis, minor axis, circularity, elongation, rounding of each particle in samples of different granulometries. From these results, it was possible to determine and characterize the parameters proposed in this study such as equivalent diameter, particle volume, sphericity, surface area, and particle mass, besides being able to determine that the grains are coarse sand.